1965
DOI: 10.2172/4633626
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Decoupling, Full and Partial

Abstract: An underground explosion in a cavity is said to be fully decoupled if the cavity is large enough for the explosion to produce only elastic motion in the walls; in a smaller cavity where the wall motion is elastoplastic, the explosion is said to be partially alecoupled. In this report, the pressure histories on the walls of cavities in salt of suitable size for alecoupling sources are calculated and used in computing the motions of the walls, including the effect of elastoplastic behavior of salt. From the moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…The effects of small cavities, however, has received much less attention than those of almost or fully decoupled tests. The theoretical studies of Patterson [1966] indicate that substantial decoupling factors are achieved even when the cavity radius is significantly smaller than that required for full decoupling. He did not investigate, however, cavities with scaled radii smaller than 14.5 m/kt 1/3.…”
Section: Testing Of Underground Nuclear Explosions Under the Provisiomentioning
confidence: 99%
“…The effects of small cavities, however, has received much less attention than those of almost or fully decoupled tests. The theoretical studies of Patterson [1966] indicate that substantial decoupling factors are achieved even when the cavity radius is significantly smaller than that required for full decoupling. He did not investigate, however, cavities with scaled radii smaller than 14.5 m/kt 1/3.…”
Section: Testing Of Underground Nuclear Explosions Under the Provisiomentioning
confidence: 99%
“…The functions C mn (r, p, q) and S mn (r, p, q) of three arguments are the real and imaginary parts of the known integrals % 1 2 3 4 5 6 7 8 9 10 11 Gnome 3.1 [15] 360 [16] 2200 [11] 4080 [11] 3120 [17] 2740 [11] 0.17 [11] 1040 895 82 4.4 7.0 6.0 Salmon 5.3 [18] 828 [18] 2240 [15] 4670 [19] 3700 [18,19] 3770 [14] 0.06 [14] 700 719 57 14.4 3. 2 3.3 which are expressed explicitly as C 00 (r, p, q) = M/R, S 00 (r, p, q) = N/R,…”
Section: Rayleigh Wavementioning
confidence: 99%
“…Herbst et al [1961] found that the cavity-pressure histories for the Cowboy series of chemical explosions are approximated by a step function plus an impulse function. Patterson [1966] showed that a cavity-pressure step function is a good approximation for nuclear explosions in cavities. Healy et al [1971] showed that a step pressure function in a spherical cavity is a good first approximation to the I•ODEAN seismic-source functions of both the tamped Salmon and the decoupled Sterling explosions.…”
Section: The Explosion Modelmentioning
confidence: 99%
“…The seismic coupling efficiencies E,/E• (Table 3) are an order of magnitude smaller than the upper limit •calculated by means of equation 20 for granite (Table 2) and are somewhat smaller than the granite coupling efficiency given in the Sipri [1968] report (see Table 2). The Fourier amplitudes of •X (t)/Ot presented in Figure 9 are for the elastic-radius step change in cavity-pressure models of the calculated Nevada (A) and Sahara (C) explosions, if we use data given in Table 3 and /Value of 4000 m 3 given for the reduced displacement potential by Patterson [1966]. possible overlap at comparable seismic-wave energies within the 0.5-to 5-Hz band is probably not sufficient to account for the (apparently) similar seismic coupling shown in Figure 7.…”
Section: Of the $Ipri [1968] Report) On The Other Hand The Differenmentioning
confidence: 99%